Study of Thermal Stability of the System and Oscillatory Modes in Newtonian Fluids (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, we studied about thermal stability in a Newtonian fluid. The theory has been applied to the study of some simple lubrication problems. According to the theory, couple-stresses are found to appear in noticeable magnitudes in fluids with very large molecules. Since the long chain hyaluronic acid molecules are found as additives in synovial fluid, Walicki and Walicka [80] modeled synovial fluid as a couple-stress fluid in human joints. A human joint is a dynamically loaded bearing which has particular cartilage as the bearing and synovial fluid as the lubricant. Normal synovial fluid is clear or yellowish and is a non-Newtonian, viscous fluid.